Analisis Fungsi Manajemen Badan Usaha Milik Desa (BUMDES) dalam Meningkatkan Pendapatan Asli Desa di Desa Saneo Kecamatan Woja Kabupaten Dompu - Andria Andria; Ega Saiful Subhan; Desi Rubiyanti (JURNAL RISET MANAJEMEN (JURMA), 2026)
This study aims to analyze the implementation of management functions of Village-Owned Enterprises (BUMDes) in increasing Village Original Revenue (PADes) in Saneo Village, Woja District, Dompu Regency. A qualitative descriptive approach was employed using interviews, observations, and documentation as data collection techniques. The informants consisted of village government officials, BUMDes managers, and community members. Data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings reveal that management functions, namely planning, organizing, actuating, and controlling, have been implemented in BUMDes management, although not yet optimally. Supporting factors include village government support, initial capital availability, management commitment, and community participation. Meanwhile, inhibiting factors include limited human resources, weak supervision systems, dependence on village funds, and limited market access. BUMDes has contributed to Village Original Revenue and supported village fiscal independence, although its contribution remains relatively limited. Therefore, strengthening managerial capacity, improving management quality, and developing more innovative business units are necessary to enhance the sustainable contribution of BUMDes to Village Original Revenue.